Innovative design for ferrofluids based parabolic trough solar collector - Alsaady, Mustafa Mohammed H (2018)
The demand for modern energy services is increasing rapidly. Solar energy has the potential to meet a significant share of the world’s energy request. Solar energy is one of the cleanest renewable forms with little or no effect on the environment. The concentrating solar power is one of the methods to harvest sun’s energy. Concentrating solar power has the advantage of easier energy storage compared to photovoltaic systems. However, the cost of energy generated by those systems is higher than conventional energy sources. It is necessary to improve the performance of concentrating solar power to make them cost competitive. Moreover, few countries such as Saudi Arabia are moving from energy based on fossil fuel to renewable energy, therefore, improving the performance of concentrating solar systems and reducing their cost is considered to emulate photovoltaic systems. This research aims to develop an innovative design of parabolic trough solar collector that uses magnetic nanofluids as a heat transfer fluid to enhance the thermal efficiency compared to conventional parabolic trough. Based on past researches, new parabolic trough design is then proposed and investigated. Ferromagnetic nanoparticles dispersed in common heat transfer fluids (ferrofluids) exhibit better thermos-physical properties compared to the base fluids. By applying the right magnetic intensity and magnetic field direction, the thermal conductivity of the fluid increased higher than typical nanofluids. Moreover, the ferrofluids exhibit excellent optical properties. The external magnetic source is installed to alter the thermo-physical properties of the fluid. This thesis is comprised of four studies including two experimental studies, one heat transfer analysis, and one economic and environmental study. A small scale parabolic trough collector was manufactured and assembled at the laboratory based on the British Standards. A steady-state method was used to measure the performance of the parabolic trough collector in corresponding studies. The performance of the ferrofluids as a heat transfer fluid was compared to the base fluid. The two experimental studies differ in the absorber used. The two absorbers used were a conventional non-direct absorber and a direct absorber without a selective surface that allows ferrofluids to absorb the incoming solar irradiation directly. The effects of nanoparticle concentration, anti-foaming, external magnetic field intensity were investigated. The volume fraction of nanoparticles was 0.05%, 0.25%, and 0.75%. Three different magnetic field intensities were investigated, 3.14 mT, 6.28 mT, and 10.47 mT. Using ferrofluids to enhance the heat transfer performance the efficiency of the ferrofluids solar collector was compared to the based fluid (water). The results show that the parabolic trough solar collector in the experiment has similar performance of flat-plate solar collectors. The efficiency of the collector improved when ferrofluids water used compared to water. Ferrofluids with low concentration improved the performance of the solar collector. The ferrofluids showed much better performance at higher reduced temperature with lower overall heat loss coefficient. Due to the non-Newtonian behaviour of the fluid, increasing the volume fraction of particles will suppress the enhancement. The pH of ferrofluids influences the behaviour of the fluid. pH values higher than 5 showed a Newtonian behaviour of the fluid. In the presence of magnetic field, the performance of the solar collector enhanced further. By increasing the magnetic field intensity, the absorbed energy parameter increased, and at higher magnetic field intensity, the rate of enhancement decreases due to the magnetic saturation of ferrofluids. In this study, the performance of non-direct absorption receiver was better than the direct absorption receiver. However, the performance of the collector with a direct absorption receiver and using ferrofluids in the presence of the external magnetic field in some cases was higher than the performance of non-direct receiver with water as heat transfer medium. The performance of ferrofluids based parabolic trough collector was theoretically investigated. The correlation, equations, and specifications used in the model were discussed in detail. The model was used to study two different parabolic trough designs. First, the parabolic trough was validated with the experimental results of AZTRAK platform. The results of the model show a good agreement with the experimental data. Thereafter, nanoparticles were added to the heat transfer fluid, and the performance of the collector with and without the presence of external magnetic field was determined. The performance of the collector did not change a lot unless the external magnetic field was present. Moreover, the effect of the glass envelope on the performance was observed. A glass cover with vacuum in the annulus has higher performance and less thermal loss. Second, the model was used to study the performance of the test rig ferrofluids based parabolic trough. The performance of the parabolic trough was first considered as concentrating collector and then as a non-concentrating collector. With the lack of an external magnetic field, the efficiency changed slightly, wherein the presence of the external magnetic field the performances of the collector enhanced and showed higher performances. In General, the presence of the magnetic field showed promising enhancement. Economic and environmental effects of using ferrofluids based solar collector compared to a flat-plate collector for household water heating systems. Results show that the ferrofluids based parabolic trough has lower payback period and higher economic saving at its useful life end than a flat-plate solar collector. The ferrofluids based collector has higher embodied energy and pollution offsets tan flat-plate collector. Moreover, if 50% insertion of ferrofluids based parabolic trough for domestic hot water could be achieved in Tabuk over 83,750 metric Ton of CO2 could be eliminated.